1979
DOI: 10.1002/star.19790310706
|View full text |Cite
|
Sign up to set email alerts
|

Improving of Egyptian Rice by Means of Gamma Irradiation

Abstract: Gamma irradiation caused reduction in cooking time with rice grains. Improvement in texture, flavor and appearance was observed. Irradiation caused degradation of starch molecules followed by decrease of viscosity of rice starch. Irradiated rice became more soluble, and its swelling capacity was decreased. These changes enhanced the extent of softening upon cooking and shortened cooking time. Degradation of the thin protein film that covers rice starch granules due to irradiation is confirmed by the increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…These results indicated an increase of solubility because of depolymerization of the starch chain (Deschreider, 1960). El Saadany et al (1979) also observed an increase in rice starch solubility as dose levels increased. The increase in wheat starch solubility on irradiation has been attributed to losses of molecular weight components formed by starch degradation (MacArthur and D'Appolonia, 1984).…”
Section: Effects Of Gamma-irradiation Variety and Storage On Starch mentioning
confidence: 71%
See 2 more Smart Citations
“…These results indicated an increase of solubility because of depolymerization of the starch chain (Deschreider, 1960). El Saadany et al (1979) also observed an increase in rice starch solubility as dose levels increased. The increase in wheat starch solubility on irradiation has been attributed to losses of molecular weight components formed by starch degradation (MacArthur and D'Appolonia, 1984).…”
Section: Effects Of Gamma-irradiation Variety and Storage On Starch mentioning
confidence: 71%
“…The increase in soluble starch content of residual cooking water (Table 3) with increase in dose levels suggested the degradation of the starch grain structure. These results indicated an increase of solubility because of depolymerization of the starch chain (Deschreider, 1960). El Saadany et al (1979 also observed an increase in rice starch solubility as dose levels increased.…”
Section: Effects Of Gamma-irradiation Variety and Storage On Starch mentioning
confidence: 90%
See 1 more Smart Citation
“…Wang et al (1983) have reported no change in cooking quality of rice up to a 3 kGy dose. Elasaadany et al (1979) and Sabularse et al (1991) have shown a slight reduction in cooking time of rice at doses of more than 1 kGy.…”
Section: Discussionmentioning
confidence: 98%
“…(1983) have reported no change in cooking quality of rice up to a 3 kGy dose. Elasaadany et al . (1979) and Sabularse et al .…”
Section: Discussionmentioning
confidence: 99%